SLAVO-GERMANIC LITERARY TRAGIFARCE – POST(-)COLONIAL CONFRONTATION OF EAST AND WEST IN THE WORKS OF ANDRZEJ STASIUK - Kalin, Arkadiusz (Porównania, 2014)
In the article I look at the confrontation between East and West in the works of Andrzej Stasiuk through the context of post colonialism – both understood as an original cultural diagnosis and as a method of reading the writer’s works. Firstly, mythologizing “little homeland”, secondly, designing “the great motherland” of Central Europe, Stasiuk finally made a step toward describing and confronting Polish (Slavic, Central European) and German (Western) cultural and psychological experience (plays Night. Slavo-Germanic medical tragifarce, Dark Woods and the quasi-travelogue book Dojczland). The latter works are examples of cross-border stories in which ethnic clichés (auto- and heterostereotypes) resulting from centuries-old relationship became not only the main literary subject but also a creative method, with the help of humour and irony, as well as provocation.